Cooperative Learning Type Group Investigation on Critical Thinking Ability at PGSD Students - Kurniasih, Anisa; Sartono, E. Kus Eddy; Adi, Banu Setyo; Gularso, Dhiniaty (Universitas Pendidikan Ganesha, 2024)
The minimum skill of students in critical thinking to solve a problem can be an obstacle in teaching and learning processes and development of their intellectual potential. This research aims to analyze how much influence the cooperative learning type group investigation model has on student critical thinking skills in social studies courses. This research uses a quasi-experimental two-group pretest-posttest design with a sample of 63 with 34 students (experimental class) and 29 students (control class). Data were collected through observation method and tests (pre-test and post-test). Data were analysed using quantitative descriptive analysis techniques, while hypothesis testing was conducted using the Wilcoxon method. The results showed that the hypothesis tested via Wilcoxon test was in the control class where the analysis results indicated a significance value of 0.071 in the control group and a significance value of >0.001 in the experimental group. Thus, the result in the experimental class is >0.001 which is >0.05, there is a difference in the group investigation type cooperative learning model on students' critical thinking skills in class A6-23. The results indicated that group investigation, as a cooperative learning model is effective in improving student critical thinking skills.